The Effect of Different Diameter Rotor Bars Size on Performance of 0.5 Hp Induction Motor - Yanawati Yahya; Muhammad Khairul Hisyam Jarail; Dina Maizana; Ibrahim Alhamrouni; Mohd Badrulhisham Ismail (International Journal of Integrated Engineering, 2024)
Induction motors are currently the most widely used industrial motors. In the field of industry, its self starting, tiny size, light weight, excellent effectiveness, minimal maintenance requirements, and simplicity to operate, less prone to accidents, and low cost per same power rating make it suitable for use. A fractional horsepower to thousands of horsepower is available. Induction motors can be found in centrifugal pumps, conveyors, compressor crushers, drilling machines, fans, blowers, escalators, refrigerators, and electric vehicles. In Malaysia, industrial motors consume 48% of total energy. In many industrialized countries, electric motors consume over 70% of the total energy. This study examines 4-pole, 0.5-hp, 50Hz, and 415V industry low-voltages 3-phase induction motors. Changing the diameter of the rotor bars is used to research how to increase the effectiveness of energy. The work proposed a new rotor design with modified bar sizes. This research was conducted utilizing two techniques: MATLAB programme simulation and theoretical calculation. Simulations show that the new design is significantly more energy efficient. The theoretical calculation was done using MATLAB. Through MATLAB programme, the effectiveness of the three rotor bar diameters and the suggested new model were compared. The finding indicated that the rotor bars with 0.648-inch diameters have a batter efficiency of 79.66% as compared to others with different diameters. Based on the simulation, the smaller the diameter of the rotor bar is more effective relative to the bigger rotor bar diameter based on a decent range of maximum rotor core flux density, which is less than 1T. The result is proven using MATLAB.